O olhar feminino sobre o cuidado à saúde da mulher quilombola - Prates, Lisie Alende (2015)
Field study, descriptive, with a qualitative approach and anthropological aspect, developed in February 2014, with 13 women of a quilombola community. The study had as a matter of research: what are the meanings, feelings and care practices experienced by quilombola women of a city in the interior of Rio Grande do Sul/Brazil? , and objective to know the meanings, feelings and care practices experienced by women of a quilombola community. Focal group was used as main technique for data production. In addition, a semi-structured interview. For data record, we used the field journal. We opted for the technique of thematic content analysis of operative proposal, under the guidance of interpretive anthropology. The research project has been approved by the Research Ethics Committee, under the case number 25345113.7.0000.5346. The dissertation includes four articles. The first is the profile of the group of women participating in the study and the last three, the three categories that emerged from the results. In the second article, the objective of to know the meaning of the health care among women of the quilombola community; it was found that the meanings attributed to the health care are conditioned to work, food, hygiene, physical activity and shares of harms to health prevention, from preventive exams and of practice of safe sex. However, they face numerous difficulties to ensure that care, which involve the lack of transportation, precarious financial conditions and difficulty of access to health services; but trends in short-and long-term strategies to ensure that health care is maintained. In the third article, aimed to unveil the feelings that emerge in this group of women regarding your identity quilombola; identified the feelings of happiness and pride, besides the feeling of freedom due to life in the community. However, these sentiments also merge to feelings of impotence, anguish, frustration and insecurity, due to adverse conditions experienced by women. All the feelings and sensations manifested are influenced by the cultural contexto and are able to influence both in the meanings attributed to the health care as care practices developed in the community. Finally, in the fourth article, had the aim of investigating how they were built socioculturally the care practices among women of quilombo and were unveiled care practices developed and shared among quilombola women in different periods covering his vital cycle. In addition, women's events, as menarche, pregnancy, childbirth, puerperium and menopause were evidenced as processes that demand specific practices of care. The practices are performed from existing resources in the family and community context, and are buoyed in the prior knowledge and in women's experiences of quilombo. It is considered that this study allowed identify some limitations and advancements in the area of women's health. It is expected to stimulate reflections and discussions within the academic and professional spaces, and encourage new research on women's health, quilombola, enabling, thus, new perspectives on these women and their experiences.